OPTIMALIZATION OF SEA TURTULE AND COASTAL VEGETATION CONSERVATION THROUGH EMPOWERMENT IN SANTEN ISLAND TOURISM AWARE GROUP, BANYUWANGI REGENCY, EAST JAVA - Aditya Yudhana; Muhammad Thohawi Elziyad Purnama; Hapsari Kenconojati; Ratih Novita Praja; Citra Kurnia Putri; Audina Putri Geraldine; Fransiska Okta Zania; Ichi Arum Galerani; Aliyyah Revinda Bima Putri (Universitas Airlangga, 2023)
The potential of Pulau Santen, which has been known as a tourism beach, is increasingly visible with the large amount of infrastructure and tourism built by the local government. This was done as an effort to promote Pulau Santen as one of the best natural tourism centers in Banyuwangi. The community in Pulau Santen must be prepared as a group that is aware of the potential of their village and the sustainability of its natural tourism. Pulau Santen is also categorized as a location which every year frequently used for sea turtle nests that land on the Banyuwangi coastal areas. This is actually very contrary to the natural habits of sea turtles which prefer to make nests in quiet places without any disturbance from sound, light, and humans. Because the place used as a natural nest is a busy tourist spot, local residents must also be given insight regarding the protection of sea turtles that land on the coast of Pulau Santen as one of the wild animals protected by the Conservation Law in Indonesia. The purpose of this activity is to strengthen the awareness of Pulau Santen tourism awareness groups regarding the important role of communities around the coast to participate in wildlife conservation and their ecosystems. Through the community service activities that have been carried out, the sustainability of the program is needed so that a model of a conservation education tourist spot is formed that has the potential to improve the economy of the surrounding communities and the conservation of biodiversity in the area.